Intelligent Road - Autioniemi, J; Autioniemi, M; Casselgren, Johan; Konttaniemi, H; Sukuvaara, T; Ylitalo, R (Luleå tekniska universitet, Strömningslära och experimentell mekanik, 2015)
Project Intelligent Road is a common effort of four main partners: Rovaniemi University of Applied Sciences (RAMK), Luleå Technical University (LTU), Finnish Meteorological Institute (FMI), Kaakkois-Suomen ELY-keskus (KaS ELY) – and representatives of business sector of the region. The overall objective of the project is to support the development of business community in Northern Scandinavian region by testing and improvement of existing innovative products concerned with road safety provision in Nordic weather conditions. The specific objective of the project is to create a demo of sustainable and marketable Intelligent Road System providing location-based short-term road weather information to the road user passing by the area. Target Groups, which are directly and positively affected by the project are businesses and above mentioned project partners. All these actors have exclusive know-how in the area and are each equally important for the implementation of the project and its success. Final beneficiaries of this project are business community of the Northern Scandinavian Region; Ministry of Transport and Communications of Finland, represented by KaS ELY and Finnish Transport Safety Agency; Swedish Ministry of Enterprise, Energy and Communications; and of course local municipalities, as Luleå Municipality, and road users. Godkänd; 2015; 20150324 (johcas) CASTT - Centre for Automotive Systems Technologies and Testing